2014
DOI: 10.5897/ajmr2013.6315
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of fungicides, botanicals and bioagents against Rhizoctonia solani inciting leaf blight on turmeric (Curcuma longa L.)

Abstract: Department caused by rop. Fifty pe trict) and Me and fungicide adhuca longi tion of biom orea. Among udomonas sp owth and 100 Bavistin fun e ratio of 1:2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…Carbendazim 50 % WP in the concentration of 0.1% showed the highest growth inhibition of 95.96 % and lowest growth of pathogen (0.50 cm) when tested with R. solani. Similar observation was recorded in a study where bavistin was effective against R. solani at lower concentration in inhibiting the mycelia growth and sclerotial production [8]. It was also reported that carbendazim inhibited radial growth of R. solani by 95-100 % [9].…”
Section: Resultssupporting
confidence: 82%
“…Carbendazim 50 % WP in the concentration of 0.1% showed the highest growth inhibition of 95.96 % and lowest growth of pathogen (0.50 cm) when tested with R. solani. Similar observation was recorded in a study where bavistin was effective against R. solani at lower concentration in inhibiting the mycelia growth and sclerotial production [8]. It was also reported that carbendazim inhibited radial growth of R. solani by 95-100 % [9].…”
Section: Resultssupporting
confidence: 82%
“…Hunjan et al (2012) reported that fungicides viz., trifloxystrobin+ tebuconazole, tebuconazole and propiconazole showed higher level of efficacy against R. solani of rice in laboratory conditions. Among the new formulations, Nativo and Bavistin were individually effective against the pathogen in inhibiting the mycelia growth and sclerotial production at lower concentration (Sriraj et al 2014). Tiwari et al (2002) reported that propiconazole and hexaconazole at 1000 ppm concentration completely inhibit the radial growth Rhizoctonia solani.…”
Section: Resultsmentioning
confidence: 99%